1981
DOI: 10.1002/1520-6629(198107)9:3<204::aid-jcop2290090303>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Mental health center versus community perceptions of mental health services

Abstract: A list of 53 mental health programs and services was presented to community samples of county commissioners and mental health board members, mental health program administrators, mental health clinicians, mental health clerical staff, clients, general public, staff of agencies related to mental health, and staff of community agencies not so related with a request to (a) indicate which programs and services were being offered by the mental health agencies of the catchment area, (b) indicate the relative importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…To develop a scale for measuring satisfaction with community-based psychiatric services and to 'weight' the relevance of the various aspects by a previous measurement of expectations, as successfully achieved in other studies (Pascoe & Attkisson, 1983;Elbeck & Fecteau, 1990). Various types of expectations can be taken into consideration (Miller, 1981). In this study, to clarify the connection with satisfaction, we defined expectations as 'the importance attributed to the various aspects in order to receive satisfactory care', using a concept which appears close to both the concept of 'ideal expectations' and of the 'value' of performance (Linder-Peltz, 1982a).…”
mentioning
confidence: 99%
“…To develop a scale for measuring satisfaction with community-based psychiatric services and to 'weight' the relevance of the various aspects by a previous measurement of expectations, as successfully achieved in other studies (Pascoe & Attkisson, 1983;Elbeck & Fecteau, 1990). Various types of expectations can be taken into consideration (Miller, 1981). In this study, to clarify the connection with satisfaction, we defined expectations as 'the importance attributed to the various aspects in order to receive satisfactory care', using a concept which appears close to both the concept of 'ideal expectations' and of the 'value' of performance (Linder-Peltz, 1982a).…”
mentioning
confidence: 99%
“…Other assessment procedures do not provide the detailed information about the values and beliefs for support or opposition that our procedure does (Hagedorn, Beck, Neubert, & Werlin, 1976; Johnson & Beditz, 1981; Miller, 1981; Shadish et al, 1982). Only our procedure used the more predictive multiplicative scoring (for examples of nonmultiplicative scoring see Scheirer, 1981; Sundstrom et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of attitudes toward community-based mental health programs (Miller, 1981; Shadish, Thomas, & Bootzin, 1982) showed that even proponents of these programs had different mean values. Proponents, such as clinicians, families of clients, and administrators, had different concerns (i.e., values) reflecting their divergent roles vis à vis these programs.…”
mentioning
confidence: 99%
“…The village aimed to provide occupational training through the various branches and to instil habits and social skills through leisure activities, classes and therapies. However, in practice, many patients remained in the village for a long time, and some for many years (Miller, 1981;Zalashik, 2008).…”
Section: The Psychiatric Work Villagesmentioning
confidence: 99%
“…Concerning the therapeutic community model, senior officials and mental health officials in Israel point out, in retrospect, that the work villages could be considered a therapeutic community since they contained elements similar to this model. Among them were housing small groups of patients who maintained continuous and regular relationships with a therapeutic team, involvement of patients in social activities and work, and letting inpatients go to work in Jerusalem (Miller, 1981). For example, Dr Maller, the director of Pardesiya Bet, stated that he realized, after seven years, that the village is an example of a 'therapeutic community' which he had researched in England.…”
Section: Characteristics Of the Work Villagesmentioning
confidence: 99%